1981
DOI: 10.1002/aic.690270308
|View full text |Cite
|
Sign up to set email alerts
|

Pressure fluctuations in a fluidized bed

Abstract: = kinematic viscosity, stokes 5 (-1 P = density, kg/m3 u = superficial tension, N/m 7 = shear stress, Pa 9 = hold-up, (-) 9' = ratio d cross-sectional area of riser and downcomer, = hold-up at z = 2.25 m, (-) Indices B = bottom d = downcomer F = friction G = gas H = hydrostatic L = liquid m = manometer M = mixture W ?-= riser, relative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(79 citation statements)
references
References 8 publications
6
71
0
2
Order By: Relevance
“…This shows that, even in the multiple bubble regime, one frequency component always stands out from the others. Keeping in mind that pressure fluctuations are caused by the occurrence of air bubbles in the solids bed (Fan et al, 1981), the power spectra suggest that of the bubbles of different sizes, especially in the bubble fluidized bed, one in particular is found in larger numbers, thus standing out in relation to the others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that, even in the multiple bubble regime, one frequency component always stands out from the others. Keeping in mind that pressure fluctuations are caused by the occurrence of air bubbles in the solids bed (Fan et al, 1981), the power spectra suggest that of the bubbles of different sizes, especially in the bubble fluidized bed, one in particular is found in larger numbers, thus standing out in relation to the others.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements are easy to make, requiring a single pressure transducer connected by a small tube to a measurement point in the bed usually a hole in the wall of the column (Brown and Brue, 2001). Fluidization regimes described above, which are closely related to bubble size, bubble rising velocity and the motion of the bed surface with time, strongly influence in fluctuation pressures (Fan et al, 1981). Therefore, the pressure fluctuations in a fluidized bed provide potential information about what is happening inside the fluidization column, because of its approximate relationship with the fluidization state (Kage et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there has been much debate about the origin of pressure fluctuations measured in fluidized beds (e.g., Fan et al, 1981, Musmarra et al, 1995, Bi et al, 1995, M"chirgui et al, 1997, van der Schaaf et al, 1997 with most of the attention aimed at bubbling beds. It appears that the measured pressure signal is a combination of (1) local bubble passages and (2) non-local compression waves; the latter resulting from a number of hydrodynamic phenomena.…”
Section: Origin Of Pressure Fluctuationsmentioning
confidence: 99%
“…They used the time lag from the cross-correlation function and the distance between probes to calculate the propagation velocity of the pressure wave. Fan et al 16 used these two functions in a similar manner. Clark et al 17 also discussed the autocorrelation function, power spectral density, and fast Fourier transform techniques and provided examples of each with a slugging fluidized bed.…”
Section: Pressure Fluctuation Analysis Techniquesmentioning
confidence: 99%
“…Other researchers have experimentally confirmed this relationship for bed depths extending to over 1000 particle diameters. 16,18,19 Sun et al 20,21 developed a relationship in which the frequency was inversely proportional to the bed diameter, but subsequent work by Bi and Grace 22 showed that the appropriate independent variable was the bed height.…”
Section: Pressure Fluctuation Characteristics In the Frequency Domainmentioning
confidence: 99%